Analysis of various degradations of five years aged mono c-Si, poly c-Si, and thin-film photovoltaic modules from rooftop solar installations in Dhaka’s tropical wet and dry climate conditions - Hossion, Abul; Manoj Kumar, Nallapaneni; Bajaj, Mohit; Alrashed, Mohammed M.; Elnaggar, Mohamed F.; Kamel, Salah (Frontiers in Energy Research, 2023)
This study evaluates the degradation of mono, poly, and thin-film silicon solar photovoltaic (PV) modules through visual and electrical measurements in Dhaka’s tropical wet and dry climate conditions. For this, several sites of rooftop solar PV installations in Dhaka, aged at least 5 years, were selected for field investigation. A visible inspection for visual degradation followed by experimental testing on various electrical characteristics of the PV modules installed on the rooftop using a portable Seaward I–V Tracer for measuring the electrical degradation was done. The electrical data were used to evaluate the degradation of short circuit current, open circuit voltage, fill factor, and maximum power in the field as compared to the nameplate values. Experimental results showed the varying types of visual degradation types such as visible cracks, snail trails, moisture intrusion, front glass, and discoloration for the investigated PV modules. The degradation of PV modules in terms of short circuit current was 0.7%/year for 85Wp mono c-Si, 7.6%/year for 150Wp poly c-Si, and 9.7%/year for 105Wp silicon thin-film, respectively. We believe this study would guide the maintenance of the solar PV systems installed on Dhaka city’s rooftop buildings.